FOXO Regulates Neuromuscular Junction Homeostasis During Drosophila Aging - Birnbaum, Allison; Sodders, Maggie; Bouska, Mark; Chang, Kai; Kang, Ping; McNeill, Elizabeth; Bai, Hua (Frontiers in Aging Neuroscience, 2021)
The transcription factor foxo is a known regulator of lifespan extension and tissue homeostasis. It has been linked to the maintenance of neuronal processes across many species and has been shown to promote youthful characteristics by regulating cytoskeletal flexibility and synaptic plasticity at the neuromuscular junction (NMJ). However, the role of foxo in aging neuromuscular junction function has yet to be determined. We profiled adult Drosophila foxo- null mutant abdominal ventral longitudinal muscles and found that young mutants exhibited morphological profiles similar to those of aged wild-type flies, such as larger bouton areas and shorter terminal branches. We also observed changes to the axonal cytoskeleton and an accumulation of late endosomes in foxo null mutants and motor neuron-specific foxo knockdown flies, similar to those of aged wild-types. Motor neuron-specific overexpression of foxo can delay age-dependent changes to NMJ morphology, suggesting foxo is responsible for maintaining NMJ integrity during aging. Through genetic screening, we identify several downstream factors mediated through foxo-regulated NMJ homeostasis, including genes involved in the MAPK pathway. Interestingly, the phosphorylation of p38 was increased in the motor neuron-specific foxo knockdown flies, suggesting foxo acts as a suppressor of p38/MAPK activation. Our work reveals that foxo is a key regulator for NMJ homeostasis, and it may maintain NMJ integrity by repressing MAPK signaling.